Energy Consumption Impact on Economic Management: Evidence from Indonesian Economy - Pattiruhu, Jozef R.; Kriekhoff, Shella (International Journal of Energy Economics and Policy, 2022)
Globally, energy consumption has been considered the significant factor that affects economic management and needs the focus of recent studies and regulators. Hence, the present article examines the impact of renewable energy consumption (REC), fossil fuel energy consumption (FFEC), energy use, electric power consumption (EPC) and energy import on the economic management of the Indonesian economy. The present research has taken the data from world development indicators (WDI) from 1991 to 2020. The present article used the autoregressive distributed lag (ARDL) model to test the linkage among the variables and executed the Granger causality test to examine the causality association between variables. The results revealed that REC, FFEC, energy use, EPC and energy import have significant and positive linkage with the economic management of the Indonesian economy. The current article has guided the regulators that they should develop the regulators related to the economic management using effective energy consumption.